From Augmentation to Redefinition: ICT-Integrated EFL Learning Tasks Based on SAMR Framework - Nuraeni, Cicih; Setyarini, Sri; Purnawarman, Pupung (Universitas Lancang Kuning, 2025)
The integration of Information and Communication Technology (ICT) into English as a Foreign Language (EFL) education is increasingly vital for fostering twenty-first-century competencies. Although digital pedagogy has gained global momentum, few studies thoroughly examine ICT integration in classroom tasks from both instructor and learner perspectives, particularly in the context of Indonesian higher education. Addressing this gap, the present study investigates the extent and depth of ICT use in EFL classrooms through the lens of the Substitution, Augmentation, Modification, and Redefinition (SAMR) framework. Employing a qualitative case study design, data were collected from ten English lecturers and 250 students across three private universities in Jakarta via classroom observations, semi-structured interviews, and document analysis. Guided by Miles and Huberman’s interactive model, the analysis triangulated findings across multiple sources. Results indicate that ICT use is concentrated at the substitution and augmentation levels, especially for reading and listening tasks. In contrast, speaking and writing activities show more advanced integration, including instances of redefinition such as multimedia storytelling and collaborative blogging. Key barriers to deeper ICT integration include uneven digital literacy, inadequate infrastructure, and limited pedagogical training. This study contributes to digital language pedagogy by mapping language skills to SAMR stages and identifying pedagogical, institutional, and policy implications. It offers actionable insights for educators and policymakers to promote more systemic, equitable, and student-centered digital learning environments in EFL contexts.